Time-Dependent, HIV-Tat-Induced Perturbation of Human Neurons In Vitro: Towards a Model for the Molecular Pathology of HIV-Associated Neurocognitive Disorders - Gurwitz, Kim T.; Burman, Richard J.; Murugan, Brandon D.; Garnett, Shaun; Ganief, Tariq; Soares, Nelson C.; Raimondo, Joseph V.; Blackburn, Jonathan M. (Frontiers in Molecular Neuroscience, 2017)
A significant proportion of human immunodeficiency virus type 1 (HIV)-positive individuals are affected by the cognitive, motor and behavioral dysfunction that characterizes HIV-associated neurocognitive disorders (HAND). While the molecular aetiology of HAND remains largely uncharacterized, HIV transactivator of transcription (HIV-Tat) is thought to be an important aetiological cause. Here we have used mass spectrometry-based discovery proteomics to identify the quantitative, cell-wide changes that occur when non-transformed, differentiated human neurons are treated with HIV-Tat over time. We identified over 4000 protein groups (false discovery rate < 0.01) in this system with 131, 118 and 45 protein groups differentially expressed at 6, 24 and 48 hours post treatment, respectively. Alterations in the expression of proteins involved in gene expression and cytoskeletal maintenance were particularly evident. In tandem with proteomic evidence of cytoskeletal dysregulation we observed HIV-Tat induced functional alterations, including a reduction of neuronal intrinsic excitability as assessed by patch-clamp electrophysiology. Our findings may be relevant for understanding in vivo molecular mechanisms in HAND.